Halted Lymphocyte Egress via Efferent Lymph Contributes to Lymph Node Hypertrophy During Hypercholesterolemia - Tay, Meng Hwee Daniel; Lim, Swee Yeng Jason; Leong, Yew Fai Ivan; Thiam, Chung Hwee; Tan, Kar Wai; Torta, Federico Tesio; Narayanaswamy, Pradeep; Wenk, Markus; Angeli, Véronique (Frontiers in Immunology, 2019)
Hypercholesterolemia is a central component of atherosclerosis and metabolic syndrome linked to chronic inflammation and immune dysfunction. Previously, we showed that hypercholesterolemic apolipoprotein E knock out (apoE-/-) mice exhibit systemic effects including skin inflammation and hypertrophic lymph nodes (LNs). However, the mechanisms accounting for LN hypertrophy in these mice remain unknown. Here, we show that hypercholesterolemia led to the accumulation of lymphocytes in LNs. We excluded that the increased number of lymphocytes in expanded LNs resulted from increased lymphocyte proliferation or entry into those LNs. Instead, we demonstrated that the egress of lymphocytes from the enlarged LN of apoE-/- mice was markedly decreased. Impairment in efferent lymphatic emigration of lymphocytes from LNs resulted from an aberrant expansion of cortical and medullary sinuses that became hyperplastic. Moreover, CCL21 was more abundant on these enlarged sinuses whereas lymph levels of sphingosine 1 phosphate (S1P) were decreased in apoE-/- mice. Normal LN size, lymphatic density and S1P levels were restored by reversing hypercholesterolemia. Thus, systemic changes in cholesterol can sequester lymphocytes in tissue draining LNs through the extensive remodeling of lymphatic sinuses and alteration of the balance between retention/egress signals leading to LN hypertrophy which subsequently may contribute to poor immunity. This study further illustrates the role of lymphatic vessels in immunity through the regulation of immune cell trafficking.